My war gone by, I miss it so - Loyd, Anthony (Penguin Books, 2001)
Nothing can prepare you for Anthony Loyd's portrait of war. It is the story of the unspeakable terror and the visceral, ecstatic thrill of combat, and the lives and dreams laid to waste by the bloodiest conflict that Europe has witnessed since the Second World War.